A case of 20-week abortion in a rare communicating rudimentary horn of a misinterpreted unicornuate uterus, incorrectly diagnosed as bicornuate: A serious hazard!. (April 2019) - Della Corte, Luigi; Fabozzi, Annamaria; Giampaolino, Pierluigi; Saccone, Gabriele; Pizzuti, Laura Micol; Romeo, Valeria; Maurea, Simone; Bifulco, Giuseppe
Abstract: Female genital malformations, as the unicornuate uterus, are deviations from normal anatomy that could impair the reproductive potential of a woman or her health. We present a rare case of a 20-week spontaneous abortion in a 24 years old patient affected by a misunderstood unicornuate uterus with communicating rudimentary horn, previously diagnosed as bicornuate, and for this reason subjected to induction of abortive labor, using mifepristone and gemeprost. Following the ultrasound exam and MRI, performed due to the failure of the abortive procedure, revealed the diagnosis of unicornuate uterus with (not clear) communicating accessory horn pregnancy, then treated with laparotomy. 3D-ultrasonography, and above all MRI, should be performed in all those cases of suspected uterine anomalies, especially in presence of pregnancy or abortion, with the aim of avoiding wrong treatments, which leads to a high risk of uterine rupture. In this case, given the uncertainty of imaging exams performed in such an advanced second trimester of pregnancy, only the surgical approach was able to discover the real communication.